Effect of a period of Selected SMR/Theta Neurofeedback Training on Visual and Auditory Reaction Time in Veterans and Disabled Athletes - S. Parsaee; S. Alboghbish; H. Abdolahi; R. Alirajabi; A. Anbari (Afarand Scholarly Publishing Institute, 2018)
Aims: Reaction time is one of the most accurate indicators for evaluating speed and efficiency of decision making in different situations, especially sport situations. This study aimed to investigate the effect of neurofeedback training on the visual and auditory reaction time of veterans and disabled athletes. Materials & Methods: In this semi-experimental study with pre-test-post-test design in 2017, 16 veterans and disabled people in Shiraz, were selected by convenience sampling. They were randomly divided into two experimental and control groups. The experimental group participated in 15 sessions of neurofeedback training with Vilistus tool and enhancement sensorimotor rhythm (SMR) protocol and declining Theta. All the participants performed a simple and selective reaction time in visual and auditory, before and after the beginning of the training. Data were analyzed by SPSS 21 using mixed analysis of variance, analysis of variance with repeated measure and LSD post hoc tests. Results: Neurofeedback training reduced reaction time in visual simple (p=0.007), auditory simple (p=0.001), visual selective (p=0.003), and auditory selectivity (p=0.0001). Conclusion: Neurofeedback training is effective on improving brain functions for simple and selective reaction time during visual and auditory in veterans and disabled athletes.